NLRP3 inflammasome of renal tubular epithelial cells induces kidney injury in acute hemolytic transfusion reactions. Issue 3 (30th March 2021) - Liu, Zhixin; Chen, Yaozhen; Niu, Bing; Yin, Dandan; Feng, Fan; Gu, Shunli; An, Qunxing; Xu, Jinmei; An, Ning; Zhang, Jing; Yi, Jing; Yin, Wen; et al.
Abstract: Background: Blood transfusion, a common basic supporting therapy, can lead to acute hemolytic transfusion reaction (AHTR). AHTR poses a great risk to patients through kidney function damage in a short time. Previous reports found that heme from destroyed red blood cells impaired kidney function, and NLR family pyrin domain containing 3 (NLRP3) inflammasome was augmented in case of kidney injury. However, the detailed mechanism regarding whether NLRP3 inflammasome is involved in kidney function injury in AHTR is not fully understood yet. Methods: Hemolysis models were established by vein injection with human blood plasma or mouse heme from destroyed red blood cells. The injured renal tubular epithelial cells (RTECs) were evaluated by tubular damage markers staining in hemolysis models and in primary RTECs in vitro . The activation of NLRP3 inflammasome in RTECs by hemes was investigated by Western blot, ELISA, scanning electron microscopy, immunofluorescent staining, flow cytometry, and hemolysis models. NLRP3 gene knockout mice were employed to confirm these observations in vitro and in vivo. The binding between a novel inhibitor (66PR) and NLRP3 was affirmed by molecule docking and co‐immunoprecipitation. The rescue of 66PR on kidney function impairment was explored in murine hemolysis models. Results: We found that heme could activate NLRP3 inflammasome in RTECs to induce kidney function injury. NLRP3 gene knockout could prevent the damage of RTECs caused by hemes and recover kidney function in AHTR. Moreover, NLRP3 inflammasome chemical inhibitor, 66PR, could bind to NLRP3 protein and inhibit inflammasome activation in RTECs, which consequently relieved the injury of RTECs caused by hemes, and alleviated kidney function damage in the AHTR model. Conclusions: Hemes could activate NLRP3 inflammasome in RTECs, and a novel NLRP3 inflammasome inhibitor named 66PR relieved kidney function damage in AHTR. Our findings provided a new possible strategy to treat kidney function failure in AHTR. Abstract : The released hemes in acute hemolytic transfusion reaction activates NLRP3 inflammasome through potassium efflux and ROS signal in renal tubular epithelial cells. Hemes from lysed RBCs induces pyroptosis and IL‐1β release of renal tubular epithelial cells in acute hemolytic transfusion reaction. The 66PR chemical inhibits hemes' activation of NLRP3 inflammasome in renal tubular epithelial cells to protect kidney function.